2019
DOI: 10.1029/2019ja027462
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to Special Issue on “Long‐Term Changes and Trends in the Middle and Upper Atmosphere”

Abstract: This special issue reports the latest results on long-term variations and trends in the middle and upper atmosphere, in particular, in the mesosphere and thermosphere. The issue is based on selected papers from the 10th IAGA/ICMA/SCOSTEP workshop on Long-term changes and trends in the atmosphere, held in Hefei, China, 14-18 May 2018. This introduction highlights recent progress in key science areas of long-term changes in the upper atmosphere.In this preface, we highlight recent progresses and provide solicita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Recently, Laštovička (2017) updated a review of progress in long‐term trends in the upper atmosphere. Yue et al (2019) reported the latest results on long‐term variations in the mesosphere and thermosphere. It appears that the long‐term temperature trends as well as its solar responses in the mesosphere are not uniform in magnitude but mostly agree in sign with the negative temperature trend and the positive solar response.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Laštovička (2017) updated a review of progress in long‐term trends in the upper atmosphere. Yue et al (2019) reported the latest results on long‐term variations in the mesosphere and thermosphere. It appears that the long‐term temperature trends as well as its solar responses in the mesosphere are not uniform in magnitude but mostly agree in sign with the negative temperature trend and the positive solar response.…”
Section: Introductionmentioning
confidence: 99%
“…Observational and simulation studies have revealed that the global mean temperature trend is cooling in the mesosphere and lower thermosphere (MLT) (Beig et al, 2003;Laštovička et al, 2006;Yue et al, 2019b;Laštovička, 2023). The cooling trends observed in the MLT region are mainly caused by the increasing anthropogenic greenhouse gases such as carbon dioxide.…”
Section: Introductionmentioning
confidence: 99%
“…Here the long-term variations mean the linear term or linear change in a regression model and on a timescale longer than one solar cycle in the middle and upper atmosphere. The long-term variations of the middle and upper atmosphere have received attention due to greenhouse-gas-driven anthropogenic climate change and its influences on atmospheric drag and thus our space vehicles (Beig et al, 2003(Beig et al, , 2008Laštovička, 2017;Yue et al, 2019b;Mlynczak et al, 2022;Zhang et al, 2023). The intraannual variations mainly include annual (AO), semi-annual (SAO), and ter-annual (TAO) oscillations.…”
Section: Introductionmentioning
confidence: 99%